Minimum International Standards of Protection Against Abuse and Harmful Religious Practices - Czubik, Paweł (Religion and Children’s Rights, 2025)
Abstract:The impact of religion on society is obvious. Also, children, the weakest yet most valuable social links, ensuring the future persistence of social and national communities, are greatly culturally influenced by the religion of their parents or guardians. The right of parents to raise their children in the faith of their ancestors is the basis of modern civilization. On the other hand, some of the world’s religions create certain risks to a child’s psychological or physical well-being. Practices that are linked more or less formally to religion can directly threaten a child’s proper biological development. They can also deprive a child of the proper experience of childhood. Such practices as genital mutilation of girls or forced child marriage characterize the main, though not exclusive, world based on the religion of Islam. The religious origins of these phenomena require deeper analysis. The norms of international law try to introduce a certain standard of child protection, to which this text is also devoted. One may doubt it is sufficient, in view of the scale of the entrenchment of violent tradition in some religious communities. Keywords: sharia, Quranic norms, political Islam, genital child mutilation, forced child marriage, parental abduction